SEMIGELANGGANG TERNER: KONSEP DAN CONTOH MENGGUNAKAN HIMPUNAN MATRIKS - Tuhfatul Janan (PT Innovative Academic Journals, 2025)
Ternary semiring was first introduced by Dutta dan Kar in 2003. Ternary semiring is a generalization of ternary ring. Ternary semiring is an algebraic structure consisting of a nonempty set together with a binary operation, called addition and a ternary multiplication, which forms a commutative monoid relative to binary addition, monoid relative to ternary multiplication, and the left, lateral, and right distributive laws hold. In this research, we use method of literature study on article which have published in international journal. In this research, we study more several parts of research from Dutta and Mandal about 2-primal ternary semirings, but will focus only on ternary semiring, including some ideals, prime radical, nilpotent element, super nilpotent ternary semiring, and 2-primal ternary semiring. Next, a more detailed discussion will be provided and accompanied by several examples using sets of matrices.